Analisis Kualitatif Pengembangan dan Implementasi Media Pembelajaran Berbasis Teknologi dalam Pendidikan Agama Islam (PAI): Studi Meta-Publikasi 2022–2025 - Ivana Deviyanti (TEKNO AULAMA: Jurnal Teknologi Pendidikan Islam, 2025)
This study employs a qualitative meta-analysis to examine the trends, implementation, pedagogical implications, and challenges of integrating technology into Islamic Religious Education (PAI) from 2022 to 2025. The methodological framework combines the perspectives of contemporary experts with modern analytical approaches. Thematic analysis identifies four key trends: systematic digitalization, immersive learning, integration of Islamic values, and multidisciplinary collaboration. Technology integration has proven to enhance accessibility, engagement, and learning relevance, yet faces persistent challenges such as infrastructure limitations, teachers’ digital literacy gaps, and curriculum misalignment. The study recommends a comprehensive transformation strategy that harmonizes technological innovation with Islamic spiritual values to achieve adaptive, moderate, and sustainable PAI learning. These findings are expected to serve as a foundation for the development of visionary and inclusive technology-based Islamic education policies.